HUBUNGAN KESIAPAN KEHAMILAN DENGAN KEJADIAN POST PARTUM BLUES PADA IBU NIFAS DI RSIA PRIMA HUSADA SIDOARJO - Hidaayah, Nur (Universitas Nahdlatul Ulama Surabaya, 2015)
A woman looking at pregnancy as a natural result marital relationship, intended and unintended. Most of the other women received a pregnancy as a natural desire and even some women, including teens, the pregnancy is the result of sexual experimentation without using contraception and pregnancy showed no preparation is a problem. This study aimed readiness relationship with the incidence of postpartum blues pregnancy on postpartum mothers in RSIA Prima Husada Sidoarjo. Methods: The study design was cross-sectional analytic, the entire population was puerperal women of 30 people, with a simple random sampling technique obtained a sample of 28 people. the independent variable is the readiness of pregnancy and the dependent variable was the incidence of post partum blues. The instruments used were questionnaires, analyzed with the chi-square statistic. Results: of the 28 respondents, there were 15 respondents were unprepared for pregnancy, most experience post partum blues events. Results of chi-square test with significance level ? = 0.05, P = 0.000 found <? = 0.05, H0 is rejected that there is a relationship with the incidence of pregnancy readiness post partum blues. Conclusion: mothers who are not ready to get pregnant may experience post partum blues. Suggestion: the provision of information about the gestation period should be given to the couple before pregnancy.